2014
DOI: 10.1038/pr.2014.136
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide: prognostic marker in congenital diaphragmatic hernia

Abstract: BackgroundB-type natriuretic peptide (BNP) has not been evaluated in newborns with congenital diaphragmatic hernia (CDH). We hypothesized that BNP and severity of pulmonary hypertension (PH) would predict clinical outcome in these infants.MethodsWe measured BNP levels and assessed severity of PH by echocardiography at one day and one week of life. Outcome was classified by status at 56 days (or prior discharge): Good (n=13) if alive on room air and Poor (n=14) if expired or receiving respiratory support. We es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…18 In patients with PHT and CDH, BNP is a strong predictor of clinical outcome. [12][13][14][15][16][17][18][19][20] BNP levels are known to correlate with the gradient of the tricuspid regurgitation jet and the ratio of tricuspid regurgitation jet gradient to mean BP. Further, BNP is weakly correlated with OI.…”
Section: Discussionmentioning
confidence: 99%
“…18 In patients with PHT and CDH, BNP is a strong predictor of clinical outcome. [12][13][14][15][16][17][18][19][20] BNP levels are known to correlate with the gradient of the tricuspid regurgitation jet and the ratio of tricuspid regurgitation jet gradient to mean BP. Further, BNP is weakly correlated with OI.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors have reported an adequate correlation between the measurement of BNP on the first day of life of NBIs with diaphragmatic hernia and their clinical course. 35 The wide dispersion of BNP levels observed in the first week of life shows the important role played by BNP during transition to extrauterine life. 7 In our study, the isolated baseline BNP value also exhibited a wide dispersion among patients.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Likewise, it is necessary to study whether these outcomes are reproducible in other facilities.…”
Section: Discussionmentioning
confidence: 99%
“…En cambio, otros autores reportaron buena correlación entre el dosaje de PNB el primer día de vida de niños con hernia diafragmática y su evolución. 35 La amplia dispersión de los valores de PNB, hallada en la primera semana de vida, muestra el importante rol del PNB durante la transición a la vida extrauteriana. 7 En nuestro estudio, el valor aislado de PNB inicial también mostró una amplia dispersión entre los pacientes.…”
Section: Discussionunclassified